2018
DOI: 10.5811/westjem.2017.10.35108
|View full text |Cite
|
Sign up to set email alerts
|

Pay It Forward: High School Video-based Instruction Can Disseminate CPR Knowledge in Priority Neighborhoods

Abstract: IntroductionThe implementation of creative new strategies to increase layperson cardiopulmonary resuscitation (CPR) and defibrillation may improve resuscitation in priority populations. As more communities implement laws requiring CPR training in high schools, there is potential for a multiplier effect and reach into priority communities with low bystander-CPR rates.MethodsWe investigated the feasibility, knowledge acquisition, and dissemination of a high school-centered, CPR video self-instruction program wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 43 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have confirmed that learning bystander CPR can improve OHCA outcomes [ 29 , 30 ]. Our study revealed that a combination of video and instruction-based CPR training is an effective method to improve the knowledge and skills of bystanders which is widely used in other contexts [ 31 , 32 ] and had similar positive effects. In addition, implementing effective training methods to increase bystander CPR knowledge may improve resuscitation in high-risk groups [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have confirmed that learning bystander CPR can improve OHCA outcomes [ 29 , 30 ]. Our study revealed that a combination of video and instruction-based CPR training is an effective method to improve the knowledge and skills of bystanders which is widely used in other contexts [ 31 , 32 ] and had similar positive effects. In addition, implementing effective training methods to increase bystander CPR knowledge may improve resuscitation in high-risk groups [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, take-home BLS training kits containing a simplified BLS training manikin are frequently used for BLS education. 26,52,117,118 Take-home BLS training kits have been used successfully by children in primary school 52,119,120 and students in high school 26,117,118,121 to pass on skills to third parties. The magnitude of the multiplier effect varies across studies, ranging from an average of 1.77 to as many as 4.9 people trained per student.…”
Section: Use Of Bls Training Manikins and Multiplier Effectmentioning
confidence: 99%
“…The magnitude of the multiplier effect varies across studies, ranging from an average of 1.77 to as many as 4.9 people trained per student. 26,117 Schoolchildren as multipliers can also reach segments of the population more likely to witness a cardiac arrest. In a Norwegian study, 43% of the population trained by high school students were ≥50 years of age.…”
Section: Use Of Bls Training Manikins and Multiplier Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…While it would be regarded as a due courtesy for the employer to cover the full cost or at least partially subsidize the cost of employee CPR training, the employer is by no means bound to cover such costs and may stipulate that CPR or first aid certification be a condition of employment [ 19 , 20 ]. We however recommend that employers should explore other options such as video-based CPR self-instruction, which is timesaving, less expensive, can be repeated more frequently, and may be more effective than traditional classroom-based CPR training courses [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%